1999
DOI: 10.1046/j.1365-2842.1999.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrognathographic and electromyographic observations on jaw depression during neck extension

Abstract: Albeit never substantiated through experimental and clinical evidence, the theoretical linchpin of the mechanics of a so-called whiplash injury of the temporomandibular joint (TMJ) is the postulate that a pre-existing depressor force (continual anchoring force), generated by the anterior suprahyoid (SH) muscles, will always act on the mandible and cause traumatic mouth opening (anterior acceleration of the TMJ condyles) when the neck is extended (posterior acceleration of the head). To test aspects of this pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
(66 reference statements)
1
7
0
1
Order By: Relevance
“…In agreement with other studies (Forsberg et al, 1985;Clark et al, 1993;McKay & Christensen, 1999), this study showed co-activation of cervical flexor and mandibular depressor/elevator muscles. The onset of myoelectrical activity in the sternocleidomastoid and anterior suprahyoid muscles showed perfect synchronism (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with other studies (Forsberg et al, 1985;Clark et al, 1993;McKay & Christensen, 1999), this study showed co-activation of cervical flexor and mandibular depressor/elevator muscles. The onset of myoelectrical activity in the sternocleidomastoid and anterior suprahyoid muscles showed perfect synchronism (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously discussed the tenuous diagnosis of a so-called whiplash injury of the temporomandibular joint, and have shown that the postulated diagnosis and postulated mechanism of injury have no foundation in basic and clinical science (Christensen & McKay, 1997;McKay & Christensen, 1998, 1999. That is to say, if a rapid injurious depression of the mandible were to occur during the first phase of a whiplash manoeuvre of the head and neck (posterior rotation of the head/extension of the neck), the motion would immediately be counteracted by a mandibular elevation, elicited through a stretch reflex in the mandibular elevator muscles (Christensen & McKay, 1997), and by the inability of the rather weak depressor muscles to anchor the mandible in space (McKay & Christensen, 1999). Nonetheless, we have recently and personally encountered the following postulate: during the first phase of a head/neck whiplash manoeuvre, the subject may voluntarily open his/her mouth to elicit a scream which, in turn, injures the jaw joints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They seem to be useful in the treatment of TMD with anterior disk displacements without reduction. 20 Manual therapy, muscle stretching, and strengthening exercises seem to be the most useful techniques. 21 We used 2 different stretching techniques.…”
Section: Discussionmentioning
confidence: 99%